The biological effects of deuterium present in food - Zoltán Répás; Zoltán Győri; Orsolya Buzás-Bereczki; László G. Boros (Discover Food)
Abstract We have evaluated the biological importance of deuterium in foods based on literature data. Deuterium is a stable isotope of hydrogen that occurs naturally in our environment and is specifically enriched in certain foods. Deuterium has specific physical and chemical properties and a high kinetic isotopic effect. Morphological and physiological changes can be observed in cells treated with deuterium, affecting fundamental processes in the body such as cell division or metabolic processes. Deuterium is naturally present in food, food products and liquids and is naturally enriched depending on the type of food. Naturally and typically, there are deuterium-poor and deuterium-rich foods. Our studies have examined the effects of this naturally occurring deuterium in the biological range on the body and concluded that deuterium ingestion is of great importance.